La estimulación temprana y su incidencia en el desarrollo de la inteligencia emocional de los niños y niñas de 4 a 5 años de edad del centro de desarrollo infantil ¨My Little Friends¨, de la ciudad de Loja. Periodo 2014 - Polo Valdivieso, Giuliana Beatriz (2015)
This thesis titled: EARLY STIMULATION AND ITS IMPACT ON THE DEVELOPMENT OF EMOTIONAL INTELLIGENCE OF CHILDREN FROM 4 TO 5 YEARS OLD OF “MY LITTLE FRIEND” DEVELOPMENT CENTER OF LOJA CITY, PERIOD 2014; has as general aim to make a scientific research on early learning and the impact it has on the development of emotional intelligence on children from 4 to 5 years old. To carry out this research the following methods were used: scientific, analytical, synthetic, inductive, deductive and statistical; and techniques such as a psychology survey directed to two teachers to establish the activities of early stimulation and emotional intelligence; and a test applied to 22 children of the institution, to evaluate the development of their emotional intelligence. 100% of teachers surveyed responded that early stimulation activities they perform are: ludic activities, motors, body expression, painting, songs, stories, drawing and plastic techniques; simultaneously, 100% of teachers report that early stimulation affects the development of emotional intelligence on children. As a result of the emotional intelligence test applied to learners, it confirmed that 59.9% of student population maintains a normal level of emotional intelligence; in high and medium level we find a coincidence of 18.18% and a level below 4.5%. For these reasons, it is suggested that in this and other early childhood centers, activities that promote the development of emotional intelligence and early learning in their students should be implemented.